THE IMPLICATIONS OF QIȘĀȘ ON JUSTICE AND SOCIAL HARMONY IN NIGERIA - Shittu, Abdulwahab Danladi (Universitas Nahdlatul Ulama Surakarta, 2025)
Abstract This paper explores the impact of qiṣāṣ on justice and social harmony in Nigeria, a nation known for its rich cultural and religious diversity. Qiṣāṣ, which underscores the principle of fair retribution in Islamic law, provides a framework for resolving conflicts and addressing grievances, thereby fostering community trust and collaboration. By analyzing its historical context and current applications, the study illustrates how qiṣāṣ can reduce cycles of violence and support restorative justice in Nigeria. The paper aims to identify the challenges and opportunities of integrating qiṣāṣ into Nigeria's legal system, incorporating perspectives from various stakeholders. Utilizing a blend of historical and descriptive research methods, the paper gathered data through interviews, observations, and literature analysis. Findings of the paper suggest that effective implementation of qiṣāṣ could greatly enhance social cohesion and improve the prospects for peace and sustainable development in Nigeria's diverse society. The paper therefore, advocates for genuine enforcement of the law in areas where it is practiced and its integration into the broader Nigerian legal framework.